Monocyte and Macrophage in Follicular Liquid: Predictive Markers of Embryo Quality in Women with Obesity and Infertility - Evgeny D. Merkulov; Anastasia V. Prozorova; Iuliia G. Samoilova; Dmitry A. Svarovsky; Kira A. Sidorenkova; Liudmila V. Spirina; Marina N. Stakheeva; Oxana S. Timofeeva; Ilya A. Petrov (Frontiers in Bioscience-Landmark)
Background: Over the past five years, the pregnancy rate in assisted reproductive technology (ART) programs in Russia has remained relatively stable. The aim of this study was to assess the distribution of monocyte and macrophage subsets in the blood and follicular fluid of infertile women undergoing assisted reproductive technology. Methods: The study involved 45 women with a mean age of 35 ± 4.66 years. Monocytes and macrophages were identified using flow cytometry. Results: We observed a decrease in the CD68+CD163+CD206+ and the CD68+CD163–CD206+ cells in patients with a body mass index (BMI) >25 by 0.19 times and 6.56 times, respectively, compared to the group with a BMI <25 (p = 0.031). Patients with fair oocyte quality had 3.6 times more oocytes than those with poor quality (p = 0.010). The relative content of CD14+163–206+ monocytes was found to be 24.15 times higher in the follicular fluid of women with poor embryo quality compared to the group with good embryos (p = 0.010). We also noted that the number of oocytes increased in women with male factor infertility (p = 0.020) and those with unspecified infertility when compared to tubal infertility. An increase in the relative content of CD14+163+206+ in the blood was higher in women with other causes of female infertility compared to those with male factor infertility (p = 0.010). The relative content of M2-monocytes (CD14+163+206–) in the blood was 4.38 times higher in women with male factor infertility than in women with unexplained infertility (p = 0.010). Conclusions: A critical component of the inflammatory reaction in patients undergoing in vitro fertilization (IVF) involves more than just the activation of pro-inflammatory cells in response to ovarian stimulation. Our research shows that changes in the distribution of monocytes and macrophages can influence embryo implantation success and pregnancy outcomes in women. These processes are influenced by various infertility-related factors, including those mentioned above. However, these findings are preliminary and require further investigation.